2020
DOI: 10.1111/1759-7714.13756
|View full text |Cite
|
Sign up to set email alerts
|

Dabrafenib and trametinib therapy in an elderly patient with non‐small cell lung cancer harboring the BRAF V600E mutation

Abstract: Dabrafenib and trametinib therapy for BRAF V600E-mutant non-small cell lung cancer (NSCLC) has demonstrated strong antitumor effects in clinical trials and has been approved for use in clinical practice. However, the efficacy and safety of this combination therapy in elderly patients remain unclear. An 86-year-old male patient, who had been diagnosed with lung adenocarcinoma with the BRAF V600E mutation, received dabrafenib and trametinib combination chemotherapy. The tumor shrunk rapidly; however, therapy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In Asian population, Ota et al reported a successful treatment of BRAF /MEK inhibitors in a female patient with V600E BRAF ‐mutated lung adenocarcinoma 19 . Another study from Japan also reported the efficacy of dabrafenib combined with trametinib in an 85‐year‐old patient with V600E mutation 20 . However, the use of targeted therapies in non‐V600E BRAF ‐mutated NSCLC was considered controversial although about 50% of all BRAF ‐mutated patients were reported to be non‐V600E‐genic type 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asian population, Ota et al reported a successful treatment of BRAF /MEK inhibitors in a female patient with V600E BRAF ‐mutated lung adenocarcinoma 19 . Another study from Japan also reported the efficacy of dabrafenib combined with trametinib in an 85‐year‐old patient with V600E mutation 20 . However, the use of targeted therapies in non‐V600E BRAF ‐mutated NSCLC was considered controversial although about 50% of all BRAF ‐mutated patients were reported to be non‐V600E‐genic type 12 …”
Section: Discussionmentioning
confidence: 99%
“…19 Another study from Japan also reported the efficacy of dabrafenib combined with trametinib in an 85-year-old patient with V600E mutation. 20 However, the use of targeted therapies in non-V600E BRAF-mutated NSCLC was considered controversial although about 50% of all BRAF-mutated patients were reported to be non-V600E-genic type. 12 Chemotherapy has showed limited results in the treatment of previously untreated BRAF-mutant NSCLC.…”
Section: Discussionmentioning
confidence: 99%